2016
DOI: 10.1111/ecog.01932
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of terrestrial assemblage turnover within and among land uses

Abstract: Land use has large effects on the diversity of ecological assemblages. Differences among land uses in the diversity of local assemblages (alpha diversity) have been quantified at a global scale. Effects on the turnover of species composition between locations (beta diversity) are less clear, with previous studies focusing on particular regions or groups of species. Using a global database on the composition of ecological assemblages in different land uses, we test for differences in the between-site turnover o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 48 publications
5
98
0
1
Order By: Relevance
“…2, Supplementary material Appendix 1 Fig. This is in line with previous studies that have correlated some measurement of dissimilarity in current 'environmental heterogeneity' with compositional dissimilarity in species assemblage composition (Buckley and Jetz 2008, He et al 2009, Newbold et al 2016. This is in line with previous studies that have correlated some measurement of dissimilarity in current 'environmental heterogeneity' with compositional dissimilarity in species assemblage composition (Buckley and Jetz 2008, He et al 2009, Newbold et al 2016.…”
Section: Influences Of Current and Past Dissimilarities In Photosynthsupporting
confidence: 88%
See 1 more Smart Citation
“…2, Supplementary material Appendix 1 Fig. This is in line with previous studies that have correlated some measurement of dissimilarity in current 'environmental heterogeneity' with compositional dissimilarity in species assemblage composition (Buckley and Jetz 2008, He et al 2009, Newbold et al 2016. This is in line with previous studies that have correlated some measurement of dissimilarity in current 'environmental heterogeneity' with compositional dissimilarity in species assemblage composition (Buckley and Jetz 2008, He et al 2009, Newbold et al 2016.…”
Section: Influences Of Current and Past Dissimilarities In Photosynthsupporting
confidence: 88%
“…In contrast to previous PREDICTS-based studies that used discrete measures of current land use and land-use intensity (Newbold et al 2015(Newbold et al , 2016, we used a continuous measure of between-site dissimilarity in remotely-sensed photosynthetic activity that summarises (inter-and intra-annual) vegetation dynamics in a single metric (the BC EVI ). In contrast to previous PREDICTS-based studies that used discrete measures of current land use and land-use intensity (Newbold et al 2015(Newbold et al , 2016, we used a continuous measure of between-site dissimilarity in remotely-sensed photosynthetic activity that summarises (inter-and intra-annual) vegetation dynamics in a single metric (the BC EVI ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that assemblages in primary and secondary vegetation did not differ strongly in species richness, the differences in average range size and Simpson's evenness highlight that the similarity in species richness hides differences in abundance and species identity-sites in secondary vegetation have gained some species, particularly wide-ranged species, but lost others, particularly narrow-ranged species (Struebig et al 2013;McGill et al 2015). This illustrates a more general pattern: land-use change is not only causing a loss of species but also a shift in community composition (de Solar et al 2016;Newbold et al 2016b) towards more widespread species, resulting in biotic homogenisation (McKinney and Lockwood 1999;McKinney 2006;Ranganathan et al 2008;Karp et al 2012;Mandle and Ticktin 2013;McGill et al 2015;de Solar et al 2015). Caution is needed in interpreting our results about average range sizes, owing to collection biases in the records held by GBIF (Yesson et al 2007;Newbold 2010;Meyer et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Mackey & Currie, ). Disturbance of natural ecosystems is frequently induced by land‐use change, while the nature of diversity changes may depend on biogeographical and ecological context (Gerstner, Dormann, Stein, Manceur, & Seppelt, ; Newbold et al., , ; Queiroz, Beilin, Folke, & Lindborg, ).…”
Section: Introductionmentioning
confidence: 99%